2005
DOI: 10.1117/12.594803
|View full text |Cite
|
Sign up to set email alerts
|

Deformation analysis of Hoffa's fat pad from CT images of knee flexion and extension

Abstract: Recent advances in medicine conjecture that certain body fat may have mechanical function in addition to its classical role of energy storage. In particular we aim to analyze if the intra-articular fat pad of Hoffa is merely a space holder or if it changes shape to provide cushioning for the knee bones. Towards this goal, 3D CT images of real knees, as well as a skeletal knee model with fat simulating Hoffa's pad, were acquired in both extension and flexion. Image segmentation was performed to automatically ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…Our study found that the patients in the complete infrapatellar fat pad excision group had more anterior knee pain after 6 weeks to 1 year compared with the no infrapatellar fat pad excision group, which had no anterior knee pain up to final followup. The pain could be caused by the lack of a fat pad, which acts as a cushion between the patellar tendon and anterior surface of the tibial components [5]. This study supported findings from a previous retrospective study [16], which indicated that nearly twice the patients with complete infrapatellar fat pad excision experienced postoperative knee pain when compared with patients with no infrapatellar fat pad excision (mean followup of 5.1 years).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study found that the patients in the complete infrapatellar fat pad excision group had more anterior knee pain after 6 weeks to 1 year compared with the no infrapatellar fat pad excision group, which had no anterior knee pain up to final followup. The pain could be caused by the lack of a fat pad, which acts as a cushion between the patellar tendon and anterior surface of the tibial components [5]. This study supported findings from a previous retrospective study [16], which indicated that nearly twice the patients with complete infrapatellar fat pad excision experienced postoperative knee pain when compared with patients with no infrapatellar fat pad excision (mean followup of 5.1 years).…”
Section: Discussionsupporting
confidence: 86%
“…Scarring of the fat pad may cause patellar infera and limit ROM after TKA [6]. The fat pad acts as a cushion between the patellar tendon and anterior tibial plateau [5]. Excision of the fat pad can cause anterior impingement, anterior knee pain, and worse results after the operation [4,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the PACS systems allow only transmission and archiving of the data. It fails to provide the functionality of online network consultations [3], [4].…”
Section: Related Workmentioning
confidence: 99%
“…An important function of the IPFP is to cushion the interface between patellar tendon and the tibial plateau, especially during kneeling [34]. Of the small number of studies that have investigated the impact of TKA on the ability to kneel, only one has explicitly stated the rate of IPFP resection.…”
Section: Ability To Kneelmentioning
confidence: 99%